SLC6A2 and SLC6A4 Variants interact with Venlafaxine Serum Concentrations to Influence Therapy Outcome - Proft, F.; Kopf, J.; Olmes, D.; Hempel, S.; Schmidt, B.; Riederer, P.; Deckert, J.; Pfuhlmann, B.; Reif, A.; Unterecker, S. (Pharmacopsychiatry, 2014)
Objective: The effects of genetic variants in genes encoding the target structures of antidepressants on the therapeutic efficacy of antidepressant drugs have been investigated with unconclusive results. One possible confounding factor in most studies was the fact that drug serum concentrations had not been determined.Methods: Within a clinical setting, 56 inpatients suffering from depressive episodes in the context of either major depressive disorder or bipolar affective disorder were studied. Response to venlafaxine was assessed after 4 weeks of treatment and correlated to serum concentration and functional variants in genes encoding the norepinephrine (SLC6A2; rs28386840) and the serotonin transporter (SLC6A4; [5-HTTLPR], rs25531). Symptom change was evaluated using the Clinical Global Impression-Improvement (CGI-I) scale.Results: No association between therapeutic response, venlafaxine serum concentration (active moiety) and rs28386840 was found. In carriers of the high expressing SLC6A4 genotype (lAlA-), a poor response to venlafaxine was found significantly more often. In subsamples stratified for serum concentration this held true for patients with serum concentrations between 201 and 400 ng/mL (n=21), while in patients with sub- (≤ 200 ng/mL; n=12) and supra-recommended (> 400 ng/mL; n=23) concentrations, no significant differences were observed.Discussion: The observed association is consistent with findings of some previous studies, whereas others showed differing results highlighting the need for further investigations.
Keywords: pharmacogenomics; serotonin transporter; norepinephrine transporter; venlafaxine; serum concentration